Amylopectin small chain glucans form structure fingerprint that determines botanical origin of starch. (20th February 2017) - Jaiswal, Sarita; Chibbar, Ravindra N.
Highlights: Amylopectin structure is specific to plant species and starch granule size. Amylopectin finger print region is formed by <10 DP glucan chains. Ratio of area% of DP6:DP7, DP7:DP8 and DP7:DP9 determine fingerprint structure. Fingerprint region is useful to identify starch botanical source. Abstract: Starch granule size, shape and structure of amylopectin are species specific and influence starch properties and end-use of starch. Amylopectin glucan chain structure was used to predict the starch botanical sources. Mathematical probability for accumulation of small glucan chains DP 6–10 reveal exponential fit curve with maximum R 2 in smallest granule size starches ( Chlamydomonas, quinoa, buckwheat). Cereal and cassava showed R 2 of 0.81–0.96 while in pulses and tubers it was less than 0.7. The amylopectin small glucan chains form a unique 'finger print region' that identified starch botanical source. Differential amylopectin chain length distribution (APCLD) graphs between DP 6–80 of all species from Chlamydomonas starch distinguished five structural groups that clustered the 31 analyzed starches into four major patterns. APCLD analyses of amylopectin combined with characteristic pattern of small linear DP (6–9) glucan chains predicted the starch botanical source.